Examining The Impact of Religiosity and Competence on Accounting Fraud:The Moderating Role of Pressure in Government Sectors - Siti Nur Aisyah; Khairina Elfhana (Journal of Accounting and Auditing, 2025)
Purpose – The study exploress the influence of religiosity and competence on accounting fraud, with pressure as a moderating variable within the government sectors. This research emphasizes religiosity and competence in preventing accounting fraud Design/methodology/approach – The research employs a quantitative methods with a correlational approach. This study utilized questionnaires distributed to 53 employees Communication and Information and the Department of Education, the study employs SmartPLS and Moderated Regression Analysis Findings – Unexpectedly The results of this study reveal that religiosity has a positively and significanty influence on accounting fraud, while competence shows a negative but insignificant effect. Pressure does not significantly moderate these relationships. These results suggest a need to reevaluate how religiosity is internalized and practiced in workplace ethics Research limitations/implications – This research has several limitations. All variables used, namely religiosity and competence as independent variables, accounting fraud as the dependent variable, and pressure as a moderating variable are based on measurements via questionnaires. Thus, the data obtained only reflects the respondents' perceptions. it is recommended that they conduct further studies, considering the limitations that exist in this research. Moderating variables should be considered as independent variables, so that researchers can make more meaningful contributions to academic literature and base the development of more ethical business practices. Apart from that, the selection of different and more specific research objects, along with the involvement of a more diverse range of respondents, is also highly recommended.